2023
DOI: 10.1039/d2cy01794f
|View full text |Cite
|
Sign up to set email alerts
|

ZnIn2S4 with oxygen atom doping and surface sulfur vacancies for overall water splitting under visible light irradiation

Abstract: Previous reports have found that surface sulfur vacancies can improve the hydrogen production performance of ZnIn2S4, and oxygen atom doping can improve its water oxidation ability. However, the simultaneous introduction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…2d) showed that both TiO 2 and WO 3 were n-type semiconductors and their flat-band potentials (approximately equal to the Fermi level) were −0.44 and 0.17 eV, respectively. 3,34 Generally, the conduction band minimum (CBM) position of n-type semiconductors is 0.2 eV more negative than the flat-band potential, 2 so the CBM positions of TiO 2 and WO 3 were located at −0.64 and −0.03 eV, respectively. Based on the band gap value, it can be calculated that the valence band maxima (VBMs) of TiO 2 and WO 3 were located at 2.40 and 2.72 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2d) showed that both TiO 2 and WO 3 were n-type semiconductors and their flat-band potentials (approximately equal to the Fermi level) were −0.44 and 0.17 eV, respectively. 3,34 Generally, the conduction band minimum (CBM) position of n-type semiconductors is 0.2 eV more negative than the flat-band potential, 2 so the CBM positions of TiO 2 and WO 3 were located at −0.64 and −0.03 eV, respectively. Based on the band gap value, it can be calculated that the valence band maxima (VBMs) of TiO 2 and WO 3 were located at 2.40 and 2.72 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen is considered one of the clean energies to replace fossil fuels due to its advantages of high calorific value and pollutionfree combustion. [1][2][3] Solar energy can be converted into hydrogen energy using semiconductors for photoelectrochemical water splitting, which has attracted much attention. [4][5][6][7][8][9][10] TiO 2 is a typical n-type semiconductor, which has low-cost, stability, and non-toxic advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Since the successful application of TiO 2 in photocatalytic water splitting, 32 a large number of inorganic photocatalysts have been explored, such as oxides (NaTaO 3 , ZnO, and SrTiO 3 ), 33–35 sulfides (In 2 S 3 and ZnIn 2 S 4 ) 36–38 and oxynitrides (Ta 3 N 5 , LaTiO 2 N, and BaTaO 2 N). 39–41 Although a series of advances have been achieved in photocatalysis, they usually exhibit low quantum efficiency due to rapid carrier recombination.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, defect engineering has become a widely adopted approach for optimizing the photocatalytic activity. The S V on ZIS can trap electrons to facilitate the separation of photogenerated carriers. Moreover, S V can promote target molecules’ adsorption and reduce the reaction energy barriers, thus leading to enhanced catalytic activity . For a considerable period, the primary focus of research has been on the chemical preparation of photocatalysts that contain vacancies. For instance, self-regulated S V induced by copper atoms in ZIS nanosheets by the hydrothermal method can regulate charge separation, thus promoting photocatalytic HER activity .…”
Section: Introductionmentioning
confidence: 99%